BEHAVIOR OF POLYCYCLIC AROMATIC HYDROCARBONS AT IMPACT SHOCK: ITS IMPLICATION FOR SURVIVAL OF ORGANIC MATERIALS DELIVERED TO THE EARLY EARTH - Mimura K.; Toyama S. (My University, 2005)
Polycyclic aromatic hydrocarbons (PAHs) with a hydrous or an unhydrous mineral matrix were impacted and analyzed, to study the behavior of PAHs against shock. Results of the shock experiments suggested that volatiles discharged from the hydrous mineral did not influence the behavior of PAHs against shock. The shocked samples contained unreacted starting PAHs, soot-like materials insoluble in dichloromethane, and secondarily formed PAHs with molecular weights ranging from 128 to 404. Approximately 95% of starting PAHs decomposed at ~30 GPa and the dominant product was the soot-like materials. Formation mechanisms of the shock products were explained by reaction processes under static high pressure-temperature conditions (e.g., carbonization, radical addition reaction, ring cross linking, and methylation). We applied these results to estimate the survival degree of organic matter delivered by carbonaceous asteroids against their impact pressures at the accretion stage of early Earth. If we use a simplified homogeneous accretion model without atmosphere to represent the stage, the radius of Earth causing 30 GPa, the pressure at which PAHs almost decompose, was calculated as 2270 km (4.0 km s -1 of impact velocity) for the impact of carbonaceous asteroids. In the case of impactors striking not land but oceans on the early Earth, the impact velocity for the decomposition of PAHs was estimated to be 6.0 km s -1. These impact velocities should have been commonly realized on the early Earth, due to the airburst and the aerobreak of impactors in the dense atmosphere. The early Earth should have been a favorable environment for obtaining and maintaining a large quantity of prebiotic organic materials leading to life. Copyright © 2005 Elsevier Ltd.
Keywords: aromatic hydrocarbons; early Earth